Enhanced contamination risk assessment for aquifer management using the geo-resistivity and DRASTIC model in alluvial settings - N.J. George; O.E. Agbasi; A.J. Umoh; A.M. Ekanem; N.I. Udosen; J.E. Thomas; M.U. Aka; J.S. Ejepu (Cleaner Water)
This study employs geo-electric surveys and Vertical Electrical Sounding (VES) data, as well as a spatiotemporal assessment, to evaluate aquifer characteristics in the study area, with the main thrust of revealing significant subsurface variability, vulnerability, and the consequent contamination of an aquifer system already established to be prolific. The study employed the DRASTIC model, integrated with geophysical resistivity methods, to assess groundwater vulnerability. Using Schlumberger electrode configurations, resistivity surveys at 19 VES locations provided insights into key aquifer parameters, including depth to groundwater, aquifer media, and vadose zone impact. This approach enhanced parameter accuracy for robust vulnerability assessments.The aquifers, primarily composed of fine to gravelly sands from the Benin Formation, exhibit high porosity and permeability. However, discrepancies in transmissivity, hydraulic conductivity, and permeability point to inconsistent groundwater behavior. Groundwater vulnerability, evaluated using the DRASTIC Index (DI), is classified as moderate to high, with influencing factors such as shallow water table depth (28 %), vadose zone properties (25 %), and net recharge (20 %). Predominantly H and K curve types suggest moderate to high contamination risks, while the region's topography and arenitic lithology exacerbate vulnerability due to slower filtration rates. The study emphasizes the need for careful groundwater management, given the aquifer's susceptibility to contamination. Regular monitoring is recommended, particularly in densely populated or agriculturally active areas, to mitigate contamination risks associated with the area's high permeability, porosity, and recharge variability. The DRASTIC model improves contamination risk assessment in sedimentary environments by analyzing several factors: depth to water (DTW), net recharge (NR), aquifer media (AM), soil media (SM), topography (T), the vadose zone (IPVZ), and hydraulic conductivity (C). Among these, DTW, IPVZ, and NR were the most sensitive contributors to the DRASTIC index (DI) for assessing vulnerability. AM and SM were moderately sensitive, while T and C had minimal impact. To effectively mitigate contamination, priority should be given to DTW, AM, and SM, with less focus on T and C. These insights help in better resource allocation and sustainable aquifer management.